2023
DOI: 10.3389/fpsyg.2023.994205
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mindfulness, anxiety and depression during the COVID-19 pandemic: A meta-analysis of correlational studies

Abstract: BackgroundThe emergence of the COVID-19 pandemic has created an environment in which numerous determinants of poor mental health are intensified. Lockdown, re-lockdown, and media coverage of the spread of the virus, have the potential to contribute to increased levels of anxiety and depression. Mindfulness may act as a buffer against COVID-19-related depressive and anxiety disorders.MethodsWe conducted a systematic review and meta-analysis by searching PubMed, PsycINFO, Web of Science, and Google Scholar for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This finding is consistent with existing literature indicating that greater mindfulness is associated with less mental distress in the time of the COVID-19 pandemic (Li et al, 2023). A recent systematic review showed that mindfulness is negatively correlated with anxiety and depression (Xu et al, 2023). According to Langer (2015), dispositional mindfulness is associated with greater cognitive flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with existing literature indicating that greater mindfulness is associated with less mental distress in the time of the COVID-19 pandemic (Li et al, 2023). A recent systematic review showed that mindfulness is negatively correlated with anxiety and depression (Xu et al, 2023). According to Langer (2015), dispositional mindfulness is associated with greater cognitive flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we extracted the effect sizes for the mindfulness (+ '() ) and mental health (+ '* ) self-reports and their respective sampling variances (# %'() and # %'* ) from the meta-analytic data set. Given that this data set did not contain any information about the correlation between effects, we utilized the findings from a recent meta-analysis of the relations among several mindfulness and mental health measures (Xu et al, 2023) and assumed a correlation of . = .35 between the effects.…”
Section: Step 4: Moderator Analysesmentioning
confidence: 99%